Composition and thickness dependence of TLD relative dose sensitivity: A Monte Carlo study - Moradi, Farhad; Olatunji, Michael Adekunle; Abdul Sani, Siti Fairus; Ung, Ngie Min; Forouzeshfar, F.; Khandaker, Mayeen Uddin; Bradley, D.A. (Elsevier, 2019)
Absorbed dose sensitivity (SAD) of a dosimeter results from absorbed dose energy dependence (f) and intrinsic energy dependence (kbq) both influenced by compositional and dimensional details. Within attenuating media the SAD is also affected by the depth at which measurements are made as beam quality varies. Monte Carlo simulations allow for studying absorbed dose, importantly providing an effective means by which correction terms for detector response (frel) can be determined. Among the wide range of TLD materials that are available, most generally in particular geometries and size, the commercial products TLD-100 and TLD-100H are perhaps the types most commonly favoured by users. Comprising lithium fluoride (Li natural) co-doped with the activators Mg and Ti or Mg, Cu and P and compressed in a teflon binder to form thicknesses of from 1 mm to a few mm, these have been investigated in previous studies. For some common TLD materials available in small thickness, from 0.125 mm up to 1.000 mm, present study seeks to calculate and compare frel values obtained at different measurement depths in water relative to a reference depth. In simulating a reference radiation field, use has been made of the MCNPX code, calculation providing the correction factors at various depths in a water phantom. Results show that at sub-millimeter dimensions, the effect of detector thickness is more pronounced than the effective atomic number, Zeff, and density of the TLDs. Smaller thickness and higher Zeff TLDs need significant correction factors, with their deviation from unity increasing with the depth up to 15 cm; frel values in the range of 0.96–1.01 were obtained in this study. Perturbation resulting from the presence of the dosimeter was also evaluated in terms of dosimeter size and material composition. Although dosimeter size, density and Zeff are well-known parameters, all important in assessing the amount of perturbation, it has been shown herein that the effect of density is more pronounced than Zeff. For the particular TLDs it is also shown that 0.125 mm thick dosimeters produce a perturbation that might be considered negligible for radiation fields larger than a few centimeters. © 2019 Elsevier Ltd